Factors Affecting Social Bonding at Ramadan in the Muslim Community: A Cross-sectional Study - Kabir, Ripul; Rabby, Fazle (Journal of Islamic and Social Studies, 2025)
Fasting in Ramadan is a mandatory rule for the Muslim. The Muslim community celebrate it once a year. However, it can influence society as well as people’s life. The objective of this study was to identify the factors that affect social bonding in the Muslim community. An explanatory sequential mixed-mode research approach was used to conduct the study. Through simple random sampling, 256 Muslims were selected for the survey. Three Muslims aged 50 and above were chosen for in-depth interviews from three wards, and six (three Imams of the three mosques and three community leaders of the respective three wards) were taken for key-informant interviews. Both descriptive and inferential statistics were performed to show the relationships among the variables. For qualitative data, thematic analysis was used. The study found that Muslims strongly supported almost all the issues mentioned, with 65percent demonstrating a strong social bond. The gender, education, occupation of the family head, family income and income earner of the Muslim community showed a significant relationship with social bond (p˂.001 or p˂.05). Education (OR-2.874 CI, 1.416-5.831) and family income (OR-1.728 CI, 1.060-2.818) were two positive and strong predictors of social bond for the Muslim community. On the other hand, income earners negatively influenced social bond in the Muslim community (OR-.456 CI, .245-.847). To increase social bond in the Muslim community, the community should be involved in education programs and employment more.